High-Risk Injection-Related Practices Associated with anti-HCV Positivity among Young Adults Seeking Services in Three Small Cities in Wisconsin. (16th April 2022) - Rogers-Brown, Jessica; Sublett, Farah; Canary, Lauren; Rein, David B.; Bhat, Maithili; Thompson, William W.; Vellozzi, Claudia; Asher, Alice
Abstract: Background: Hepatitis C virus (HCV) infection has been increasing among people who inject drugs (PWID), younger than 30 years, and living in rural or suburban areas. We examined injection-related behaviors of young PWID to determine factors associated with HCV infection. Methods: From September 2013-May 2015, respondent-driven and snowball sampling were used in 3 suburban areas of Wisconsin to recruit PWID 18-29 years who reported injection drug use in the previous 12 months. Participants were tested for HCV antibody (anti-HCV) and reported injection-related behaviors/practices via self-administered computer-based survey. We calculated anti-HCV prevalence and assessed associated factors using multivariable logistic regression. Results: Forty-two percent (117/280) of participants were male, 83% (231/280) were white, and median age was 23 years. Overall HCV prevalence was 33%, but HCV prevalence among males was 39%. Adjusting for age, sex, race/ethnicity, education, relationship status, insurance status and income, anti-HCV positivity was associated with higher injection frequency (> 100 times in the past six months) (aOR = 3.07; 95% Confidence Interval (95% CI): 1.72-5.45), ever shared syringes (aOR = 5.15; 95% CI: 2.52-10.51), past week/last use receptive rinse water sharing (aOR = 1.88; 95% CI: 1.06-3.33), past week/last use receptive filter sharing (aOR = 3.25; 95% CI: 1.61-6.54), reusing syringes (aOR = 1.91, 95% CI: 1.08-3.37), history of overdose (aOR = 8.82; 95% CI: 2.26-3.95), and having ever injected another PWID (aOR = 8.82; 95%CI 3.94-19.76). Discussion: Anti-HCV positivity is associated with high-risk injection practices. Young PWID would benefit from access to evidence-based interventions that reduce their risk of infection, link those infected to HCV treatment, and provide education to reduce further transmission.